Geomorphological analysis of the south-middle coast of Chile in skylab images - Araya Vergara, José F. (Investigaciones Geográficas, 1977)
The material fron SKYLAB 190 A was examined in posirive transparences of 1 1/4 x 2 1/4 in., which belong to 6 bands. 1: was observed the better bands that are those of 0.6 - 0.7 microns (panchromatic. hlack and white), 0.5 - 0.88 microns (infrared colour) and 0.4 - 0.7 microris (high resoheion colour). The analysls furnishes fout groups of coastal individuals: A Related to the structure, B. Formed by subaerial processes little changed by the sea, C. Formed under action of factors other than waves, andD. Formed by wave ation. As regional individuals were detected two types of associations: A. Connected with the structure and tectonics and B. Connected with the external geodynamics. The regional systematization gibs two tectonic styles between Mataquito River (35°S) and Arauco (37-38° S.): A. Oblique structure in the North, and B. Longitudinal structure in the South. The dynamic notion obtained from the images teaches: A. that the coast has evolved with two different tectonic styles, B. that the river; sedimentation has been important for rhe coastal regularization, C. that de marine sedimentation is more important than the abrasion in these regularization, and D. that there is a combinate action berween the tectonics and the sea on the cliffs origin. Therefore, the comparative study of the multispectral camera irnaprs is a good method for regional studies. Some better bands may be sdected and complementarily used.The bands colour infrared and conventional, as well as the black and white panchromatic are revealed as being practical in coastal morphology.